The sanctity of life - Newman, Robert C.; Harding, William N.; Vannoy, J. Robert; MacRae, Allan A.; Grauley, John E.; Kaufmann, Donald; Clark, John P.; Taylor, Thomas V.; Murray, Jack (Bible Evangelism, 1978)
Creation, man in the image of God / R. Newman -- Capital punishment / W. Harding -- Ten commandments / R. Vannoy -- Creation, man for glory of God / A. MacRae -- Biblical sex laws / J. Grauley -- Sermon on the Mount / D. Kaufmann -- Right to live / J. Calrd -- Creation, man reborn / R. Newman -- Prophetic literature / T. Taylor -- Civil rights / T. Taylor -- The Christian's response / J. Murray.